2020
DOI: 10.1253/circrep.cr-19-0125
|View full text |Cite
|
Sign up to set email alerts
|

Cryoballoon Ablation for Patients With Paroxysmal Atrial Fibrillation

Abstract: Atrial fibrillation (AF) is the most common sustained cardiac arrhythmia in clinical practice and induces cardiac dysfunction and stroke. The development of AF requires a trigger and also an electroanatomic substrate capable of both initiating and perpetuating AF. In the past decade, ectopic beats originating from the pulmonary veins (PV) have been identified as a source of paroxysmal AF. Thus, strategies that target the PV, including the PV antrum, are the cornerstone of most AF ablation procedures. Recently,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 65 publications
0
2
0
Order By: Relevance
“…Aryana et al tested a dosing protocol guided exclusively by the TTI in 355 patients compared with 400 control patients who underwent a CBA using a conventional approach [29]. Although the current study observed the PV potentials in 32% of the PVs during the CBA procedure, the fourth-generation CB enabled better observation of the PV potentials with its shorter balloon tip than the second-generation CB [19]. In the future, the best strategy may be created by combining the TTT with TTI.…”
Section: Discussionmentioning
confidence: 59%
See 1 more Smart Citation
“…Aryana et al tested a dosing protocol guided exclusively by the TTI in 355 patients compared with 400 control patients who underwent a CBA using a conventional approach [29]. Although the current study observed the PV potentials in 32% of the PVs during the CBA procedure, the fourth-generation CB enabled better observation of the PV potentials with its shorter balloon tip than the second-generation CB [19]. In the future, the best strategy may be created by combining the TTT with TTI.…”
Section: Discussionmentioning
confidence: 59%
“…The detailed CBA methodology was previously reported [19]. In brief, general anaesthesia (laryngeal mask airway, I-gel device, Intersurgical Inc., Wokingham, Berkshire, UK) under administration of propofol and dexmedetomidine was employed, with oesophageal temperature monitoring using a multi-thermocouple temperature probe (SensiTherm, St. Jude Medical, Maple Grove, MN, USA).…”
Section: Ablation Proceduresmentioning
confidence: 99%